If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 7(x + 3) = 20 Reorder the terms: 5 + 7(3 + x) = 20 5 + (3 * 7 + x * 7) = 20 5 + (21 + 7x) = 20 Combine like terms: 5 + 21 = 26 26 + 7x = 20 Solving 26 + 7x = 20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-26' to each side of the equation. 26 + -26 + 7x = 20 + -26 Combine like terms: 26 + -26 = 0 0 + 7x = 20 + -26 7x = 20 + -26 Combine like terms: 20 + -26 = -6 7x = -6 Divide each side by '7'. x = -0.8571428571 Simplifying x = -0.8571428571
| 2+6x+4x=-8 | | x+1+x=13 | | 16n-5=4n-2 | | 2x-1=11x-65 | | 8+3x-4x=8 | | (5x-2)+(x+12)=40 | | -7x+10+x=16 | | 6x+9y=14 | | (5-2a)(11-7)-5=-9 | | 5(2x-5)+2(x-3)-4=3(x-2)-4(2-3x) | | 4.3(5.6+5)+9c= | | -8(m+2)-1.9m= | | 2x+5*2-8+21a= | | 3x+4=-2x-1 | | 3x+15-6=3x+9 | | 5x+5-5x=x+8 | | (15a-1)(1+5)-3=0 | | 10+5x=3x+18 | | 4-2x=4-2x | | 8+8x=15x+57+x | | 4x-28=6x | | 8+8x=15x+57 | | 5y*3y-12x=0 | | 40-8x=2x | | 10xy+5y*3y-12x=0 | | 4x+5=6x+7 | | (a-1)-(a+2)-(a-3)=a | | 21=6x+7y | | t+u+t+3u= | | 98-4x=-11x | | 2x(3x+1)=3x(2x+1)-2 | | 4p+2p+5q+q= |